Regional Differences in the Amino Acid Sequences of Fasciola hepatica Cathepsin L2 From a Turkish Isolate - Baspinar, Serpil; Celik, Venhar; Turgut-Balik, Dilek; Kaplan, Mustafa (Galenos Publ House, 2011)
Objective: This study describes cloning and sequence analysis of the gene coding for the cathepsin L2 gene from a F hepatica isolate from Turkey. Methods: The adult form of F hepatica was collected from the infected cattle liver and cDNA was obtained following total RNA isolation. After amplification of the gene by PCR, ligation and transformation was performed. Finally, DNA sequencing and phylogenetic analysis were performed. Results: The gene consists of an open reading frame of 981 nucleotides corresponding for 327 amino acids. There are five amino acid positions where Firat F hepatica cathepsin L2 differs from the F hepatica cathepsin L2 Dublin strain. This sequence was the first cathepsin L2 gene from a Turkey isolate and the second cathepsin L2 sequence entered into the database. A comparative amino acid sequence analysis indicated that there is about 99% homology with the F hepatica cathepsin L2 reported in the literature, 98% homology with the F hepatica cathepsin L-like protease, and 85% homology with the F hepatica cathepsin L1 isolated in the Elazig region at the nucleotide level. Conclusion: The amino acid differences between sequences could be evaluated for further immunization and diagnosis studies.
Keywords: Fasciola hepatica; cathepsin L2; nucleotide; amino acid sequence